Public Health Awareness Building in the field of Safe Motherhood - Bhatta, Badri Nath (Journal of Nepal Health Research Council, 2009)
Background: The study aims to explore the awareness level of people on safe motherhood in some selected districts and to compare the situation on the given issues among the selected districts. Methods: A total of 400 sample households (HHs) were represented from the 20 wards from 10 VDCs of four districts in the country during the fieldwork from April to August 2006. The sampled VDCs and wards were selected with the meeting of respective stakeholders from district to village levels respectively. A semi- structured questionnaire and ethnographic observation were administrated for garnering required data. Results: Out of the total respondents, the awareness level in marital age has been slightly increased in sampled communities. 29% marriages took place below the age of 18 years. 58.3% reported they married at the age of 18 to 22 years followed by above 22 years (12.5%). In case of cutting placenta, 58.9% are found to use blades followed by sterilized blades (20%) and others including sickle and knife (15%). Among them, majority people still practiced delivery at home rather than public health institutes. The study indicates that 80.5% population reported they managed home delivery followed by health institutes (18.3%). Similarly, 30% respondents expressed mothers- in- law assist during delivery. 69% informants reported that they milked colostrums to infant. Therefore, public health awareness program has to be arranged for the increase its level in some selected areas. Conclusion: Safe motherhood is the significant component of reproductive health. Uterus prolapse in Nepal is the most complicated problem in this field. Despite the various efforts, public health awareness programs have to be arranged in the critical areas of reproductive health. Key words: awareness, health education, public, safe motherhood doi: 10.3126/jnhrc.v6i2.2187 J Nepal Health Research Council, 2008 Oct; 6(13) Page: 69-73